EVALUATING PHOTOGRAMMETRIC APPROACH OF IMAGE-BASED POSITIONING - X. Li (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2012)
In recent years, researches in the domain of location-based services have increasingly focused on developing and utilizing alternative positioning techniques for in GPS-denied environment. Image based positioning technique holds good promise for such applications. In this paper, a previously proposed image-based positioning system using photogrammetric methods has been put into rigorous evaluation. The precision and accuracy of such photogrammetric approach of image-based positioning is depending on the precision and accuracy of final space resection process, which is a function of PGCP distribution and measurement accuracy, and any factor that has certain impact on either of these two major components will to certain degree influence final positioning accuracy. Therefore in this article, the way that different factors influencing the positioning accuracy are analysed through both mathematical model and experiments, which includes simulations and tests based on real data. Through evaluation of such system, we aims at better understanding image-based positioning system alike so as to find its strength, weaknesses and ways to improve the overall performance for it to realize its full potential.